Specific phenolic compounds and sensory properties of a new dealcoholized red wine with pomegranate (Punica granatum L.) extract. (September 2014) - Tárrega, Maria Amparo; Varela, Paula; Fromentin, Emilie; Feuillère, Nicolas; Issaly, Nicolas; Roller, Marc; Sanz-Buenhombre, Marisa; Villanueva, Sonia; Moro, Carlos; Guadarrama, Alberto; Fiszman, Susana
The pomegranate ( Punica granatum L.) fruit has a long history of human consumption and possesses notable antioxidant and cardiovascular properties. This work evaluated the feasibility to provide a new functional beverage based on a dealcoholized red wine matrix supplemented by a pomegranate extract. The potential bioactive compounds in the pomegranate extract, punicalagin A and B and ellagic acid, were analyzed during the downstream process in order to evaluate the functional dose in the final beverage. The addition of pomegranate extract to the dealcoholized red wine resulted in a product with more intense yeast odor, acidity, yeast flavor, and astringency and with a less intense berry flavor. Consumer acceptance of the product was also investigated and the results revealed the existence of a niche of consumers willing to consume dealcoholized wine enriched with pomegranate extract. After tasting, 50% and 40% of those consumers initially interested by this product concept declared to be interested to purchase the control sample and the functional beverage, respectively. The daily consumption of two servings of 250 mL of this new pomegranate-enriched dealcoholized wine provides 82 mg of total ellagitannins, corresponding to the sum of punicalagin A and B and ellagic acid.